Pembangunan Sistem Monitoring CCTV PT Pelindo III Cabang Tanjung Perak menggunakan Location Based Services berbasis Android - Ronny Eka Rachmad; Adam Hendra Brata; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Pelindo III is one of the State-Owned Enterprises (SOEs) engaged in transportation and logistics services providers, one of the branches is located in Tanjung Perak. In carrying out its role as a community service center, it requires strict supervision of all activities to avoid crime or supervise the performance of employees at PT Pelindo III Tanjung Perak Branch, a way of monitoring that can be done through CCTV. However, it is not easy to supervise all the CCTV that has been installed on PT Pelindo III Tanjung Perak Branch, totaling hundreds of units. Based on this case, a CCTV monitoring application was developed using an android-based map feature. The system development process was carried out using waterfall method. There were 20 functional requirements and 1 non-functional requirement for the system to be built. This application development process were tested by validation testing and unit testing with 100% valid results. Location testing is done using the Haversine Formula, with 100% valid result. The development of a CCTV monitoring application using location-based services based on android is expected to help ease workload of IT employees of PT Pelindo III Tanjung Perak Branch in monitoring all installed CCTV.